FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN PENYAKIT DIABETES MELLITUS TIPE 2 DI GAMPONG KEUDE KRUENG GEUKUEH ACEH UTARA - Said Aandy Saida; Zurriyani Zurriyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
DM is a metabolic disease with hyperglycemia criteria where the pancreas cannot produce enough insulin or effectively the body cannot use the insulin produced. In the world, International Diabetes Federation states that about 8.3% worldwide suffer from DM, by 2030 it will increase to 10%. In 2045 the prevalence of DM will reach 682 million people aged 20 to 70 years who suffer from diabetes mellitus. In Indonesia it has a prevalence of up to 9.1 million people diagnosed with diabetes and in Aceh has increased to 2.5%. The purpose of the research was to find risk factors wich related to DM type 2. This was a descriptive observasional with cross sectional with 30 samples with cases and control. Chi square test showed thet risk factors which related DM tye 2 is dietary habit (OR=1,09;95%CI1,24-0,15) and physical activity (OR=0,1246;95% CI 1,38-0,13). Logistic regression showed that dietary habits and physical activity had 64% influence to type 2 DM. The recommendations of this research are expected to be a reference for other researchers to examine different variables, locations and amounts.Keywords: Type 2 diabetes, diet, physical activity